Who knows it is a game?: on strategic awareness and cognitive ability - Fehr, Dietmar; Huck, Steffen (Experimental economics, 2016)
We examine strategic awareness in experimental games, that is, the question of whether subjects realize they are playing a game and thus have to form beliefs about others’ actions. We conduct a beauty contest game and elicit measures of cognitive ability and beliefs about others’ cognitive ability. We show that the effect of cognitive ability is highly non-linear. Subjects below a certain threshold choose numbers in the whole interval and their behavior does not correlate with beliefs about others’ ability. In contrast, subjects who exceed the threshold avoid choices above 50 and react very sensitively to beliefs about the cognitive ability of others.
Online veröffentlicht am 11. August 2015
Gesehen am 26.06.2023